Genetic and epigenetic associations with child development and mental health in a South African birth cohort - Moyakhe, Lihle (Department of Psychiatry and Mental Health, 2025)
Childhood developmental and mental disorders – including internalising and externalising symptoms – are prevalent in low- and middle-income countries (LMICs) such as South Africa. There is growing interest in the associations between polygenic risk scores (PRS), epigenetic age (EA) deviation, DNA methylation risk scores (MRS), and key neurodevelopmental disorders such as attention-deficit hyperactivity disorder (ADHD). However, most work has thus far been undertaken in high-income countries (HICs) with participants of European ancestry; and populations of African ancestry have been notably under-represented. The Drakenstein Child Health Study (DCHS), an ongoing South African birth cohort study, provides an opportunity to investigate the associations of PRS, EA deviation, and MRS, with childhood developmental and mental health outcomes, in an ancestrally diverse study population. This doctoral project aimed to investigate potential genetic and epigenetic associations with adverse developmental and mental outcomes in children. This aim was addressed via five objectives. First, a systematic review was undertaken to collate existing work (both in HICs and LMICs) on associations between PRS (the weighted sum of risk alleles) and developmental and mental health disorders in childhood and adolescence. A second systematic review focused on associations between EA deviation (relative to chronological age) and the outcomes of interest. Third, empirical analyses of DCHS data investigated the relationship between a PRS for ADHD, and child developmental outcomes, as well as internalising and externalising symptoms. Fourth, the relationship between gestational EA deviation at birth, and child developmental and mental health outcomes in the DCHS, was explored. Finally, the association between MRS (the weighted sum of methylation markers' beta values) at birth, and the outcomes of interest, was investigated. The systematic reviews adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, and standard methods were used to collate and analyse the data. In the DCHS, a PRS for ADHD was generated (target n=958) using summary statistics from the Early Genetics and Lifecourse Epidemiology (EAGLE) consortium (discovery n=17,666). Gestational EA deviation at birth and MRS were calculated using DCHS umbilical cord blood samples (n=275) and summary statistics from the Pregnancy and Childhood Epigenetics (PACE) consortium (n=2,477 for the MRS analyses). Child developmental outcomes (i.e. cognitive, language and motor development) were derived from the Bayley Scales of Infant and Toddler Development, 3rd edition (Bayley-III), and child mental health outcomes (i.e. internalising and externalising symptoms) from the Child Behaviour Checklist (CBCL). Associations of interest were investigated using bivariate and multivariable linear and logistic regression models, controlling for relevant covariates (including sociodemographic characteristics, psychosocial risk factors, child anthropometric measures and genomic principal components). In the first systematic review (of 14 studies, with ~50,000 participants), significant associations between PRS for several mental health disorders and adverse developmental/mental health outcomes were found. For example, a high ADHD PRS was found to be associated with adverse outcomes in childhood and adolescence in 5 of the 14 included studies. Additionally, 4 studies described associations between PRS for bipolar disorder and impaired cognitive function, and poor executive functioning, in children and adolescents; and 2 studies highlighted associations between schizophrenia PRS and ADHD, as well as internalising and externalising symptoms in children. In the second systematic review (of 4 studies with N~700 participants), gestational EA acceleration was found to be significantly associated with internalising symptoms in children. The empirical analyses yielded no significant genetic or epigenetic associations with the developmental or mental health outcomes of interest in the DCHS children. However, trend-level associations were observed - in both the unadjusted and the adjusted models - between gestational EA deviation at birth and child externalising symptoms (at 42 months) in the DCHS (unadjusted β = −0.19, p = 0.072; adjusted β = -0.17, p= 0.10). While limited by sample size and lack of ancestry-matched summary statistics, this work nonetheless represents a novel exploration of the potential genetic and epigenetic underpinnings of developmental and mental disorders in South African children. In future, further studies – ideally with larger sample sizes, ancestry-matched summary statistics and longitudinal developmental phenotype data – would be warranted to expand on this preliminary work. Ultimately, such research may provide insight into the genetic and epigenetic risk factors of developmental and mental health outcomes in children; and may inform targeted early interventions for at-risk children – particularly in resource-limited settings such as South Africa.